Anastomosing Haemangioma of the Kidney Involving a Segmental Branch of the Renal Vein - Ayodeji Oluwarotimi Omiyale; Anurag Golash; Amandeep Mann; Dimitris Kyriakidis; Karthik Kalyanasundaram (Case Reports in Surgery)
Anastomosing variant of capillary haemangioma is a rare and recently described vascular tumour with a proclivity for the genitourinary tract. Here we present the case of a 64-year-old man with incidental finding of 3.4 cm renal mass on CT who had laparoscopic nephrectomy with a good postoperative recovery. Histopathological diagnosis of anastomosing haemangioma of the kidney was made and the patient was followed up for 10 months without evidence of tumour recurrence.